2008
DOI: 10.1097/mlr.0b013e31817d932e
|View full text |Cite
|
Sign up to set email alerts
|

Preferences for Colorectal Cancer Screening Among Racially/Ethnically Diverse Primary Care Patients

Abstract: Primary care patients have distinct preferences for CRC screening tests that can be linked to test attributes. Racial/ethnic variations in test preferences persist when controlling for attributes. Tailoring screening recommendations to patients' preferences may increase screening adherence.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

14
139
0
1

Year Published

2009
2009
2022
2022

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 137 publications
(154 citation statements)
references
References 36 publications
(43 reference statements)
14
139
0
1
Order By: Relevance
“…24 Although we are not aware of other published studies that have compared different methods of values elicitation for CRC screening, several have used explicit techniques to assess key decisional attributes. 13,[25][26][27][28] (Details of these studies are provided in Appendix 5-available online) Most studies have found test accuracy (ability to detect cancer and polyps) to be the most common most important attribute, but the order of importance of other attributes has varied considerably across studies.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…24 Although we are not aware of other published studies that have compared different methods of values elicitation for CRC screening, several have used explicit techniques to assess key decisional attributes. 13,[25][26][27][28] (Details of these studies are provided in Appendix 5-available online) Most studies have found test accuracy (ability to detect cancer and polyps) to be the most common most important attribute, but the order of importance of other attributes has varied considerably across studies.…”
Section: Discussionmentioning
confidence: 99%
“…13,14 These attributes were used for both the choice-based conjoint analysis tasks and rating and ranking tasks.…”
Section: Development Of Attributesmentioning
confidence: 99%
“…[14][15][16] Furthermore, when these discussions are held, primary care physicians routinely recommend colonoscopy as their preferred test and rarely mention other tests. [17][18][19] Recent research, however, demonstrates that providing patients a choice of screening options may increase CRC screening completion, particularly among racial and ethnic minorities. 20 We conducted a quasi-experimental trial to evaluate and compare the effectiveness of a physician-only and a physician-patient intervention on physicians' recommendations for CRC screening and actual rates of screening.…”
Section: Introductionmentioning
confidence: 99%
“…Extending this assumption to health behavior, if there is variation in preferences regarding the most desirable attributes of a product or service across individuals and these attributes can be varied across products or services, then offering a wide variety of products or services (representing a range of potentially desirable attributes) will be preferable because it will increase the likelihood that each individual will find and act on an option that satisfies his or her unique preferences. Studies comparing preferences for four or more recommended CRC screening options do suggest there is variation in mode preferences and the value patients assign to attributes related to preferences 11,[19][20][21][22][23][24][25] . However, evidence that the vast majority of patients prefer either FOBT or colonoscopy [20][21][22][23]25 calls into question the value of investing in the more rarely preferred screening modalities, particularly in settings where high adherence rates have already been achieved using a screening approach emphasizing a single mode [26][27][28] .…”
Section: Introductionmentioning
confidence: 99%